How to develop financial applications with game features in e-banking? - Rodrigues, L. F.; Costa, C. J.; Oliveira, A. (ISDOC '13: Proceedings of the 2013 International Conference on Information Systems and Design of Communication, 2013)
As for Gamification, it is about business software with game characteristics, understanding the software development process will improve the practices, and will more than likely, improve the business itself (make it more efficient, effective, and less costly and mainly collect a positive influence from the customers). This study aims to develop a framework that provides the mechanisms to ensure that the software will have game characteristic and that clients will recognize it as Gamification. Our results show that the five-step framework proposal applied to the Gamification project management on this study, the Spiral development model, and the group discussion results into a positive effect on customers and e-business. The spiral development methodology used for the development of this application showed to be the appropriated for this type of project. The tests with discussion-groups proved to be a key "tool" to identify and adapt the game characteristics that has led to the improvement of customer perception of socialness, usefulness ease of use, enjoyment and ease of use that probed to have a strong positive impact on the intention to use the game.